Exclusivism Reflected In J.K. Rowling's The Casual Vacancy Novel (2012): A Sociological Perspective - Nopitasari, Impian; , Drs. M. Thoyibi, M.S; , Siti Fatimah, S. Pd, M.Hum (2013)
This Study is about Exclusivism. The problem of this study is how exclusivisim expressed in the The Casual Vacancy novel. The objectives of this study are to identify the characteristic of exclusivism in The Casual Vacancy novel, to describe exclusivism in The Casual Vacancy novel, and to reveal the necessity for J.K. Rowling to address exclusivism. The object of the study is The Casual Vacancy by J.K. Rowling. It used sociological perspective. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in The Casual Vacancy novel, J.K Rowling delivers message that exclusivism can lead to exploitation and oppression. Second, based on the sociological analysis, it is apparent that there is a strong relation between this novel and the social reality in England in early twenty first century.